Coral whisperers : scientists on the brink - Braverman, Irus, 1970- (Critical environments (Oakland, Calif.), 2018)
"In recent years, a catastrophic global bleaching event devastated many of the world's precious coral reefs. Working on the front lines of ruin, today's coral scientists are struggling to save these important coral-reef ecosystems from the imminent threats of rapidly warming, acidifying, and polluted oceans. Coral Whisperers captures a critical moment in the history of coral-reef science. Based on over one hundred interviews with leading scientists and conservation managers, Irus Braverman documents a community caught in an existential crisis and alternating between despair and hope. In this important new book, corals emerge as signs and measures, but also as a way out of the projected collapse of life on earth"--Provided by publisher.